2020
DOI: 10.1177/0194599820907336
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and 1‐Year Outcomes with a Slim Modiolar Cochlear Implant Electrode Array

Abstract: Objective To explore the immediate and 1-year outcomes of patients who underwent implantation with the slim modiolar electrode (SME). Study Design Consecutive case series with chart review. Setting Tertiary referral academic center. Subject and Methods Between May 2016 and August 2018, a total of 326 cochlear implantations (CIs) were performed. Intraoperative x-rays were performed in all cases to identify tip rollovers. Scalar location was identified for 76 CIs that had postoperative computed tomography recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 20 publications
4
45
1
Order By: Relevance
“…Six studies described the TF rate of the CI-532 electrode array. 12,23,[29][30][31]44 From a total of 622 implantations, 37 TFs were identified, resulting in a TF rate of 5.9% for the CI-532. Finally, for the remaining three studies, two studies reported one TF, 38,39 and one study 41 reported no TF.…”
Section: Tfmentioning
confidence: 99%
“…Six studies described the TF rate of the CI-532 electrode array. 12,23,[29][30][31]44 From a total of 622 implantations, 37 TFs were identified, resulting in a TF rate of 5.9% for the CI-532. Finally, for the remaining three studies, two studies reported one TF, 38,39 and one study 41 reported no TF.…”
Section: Tfmentioning
confidence: 99%
“…These results are an evident improvement compared to previously reported implantations via a cochleostomy approach at our center, and generally comparable to what is reported in the literature, although studies adequately reporting on the CT-evaluated scalar position by surgical approach for the SME are still relatively scarce. The studies in which this was determined using high-resolution imaging result in a combined average translocation risk of 4.8% (22/461) [4,[18][19][20][21][22][23][24]. Of these aggregated 461 participants, 396 could be identified as having been implanted using either a RW or eRW approach and 39 as implanted using a CS approach [4,18,20,21,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The slim modiolar electrodes have been reported to provide a consistently higher scalar tympani position than conventional perimodiolar electrodes 6 , 14 . In addition, 4.1–4.6% rate of tip-fold over has been reported in the literature 9 , 14 , but tend to gradually decrease with experience 15 . Thus, specifically for slim modiolar electrodes, degree of modiolar proximity may be one of the critical determinants of better auditory performance.…”
Section: Introductionmentioning
confidence: 89%